Importancia de la gestión de documentos del área de archivo y su efecto en la resolución de conflictos en el área comercial de la empresa CNT, cantón Babahoyo - Ramos Valdez, Noemi Soledad (2021)
This case study was carried out with the purpose of describing the importance of document management in the archive area and its effect on the resolution of conflicts in the commercial area of the CNT company, Babahoyo canton, since document management It is essential for the proper management in terms of order, classification and storage of the same, benefiting in the optimization of secretarial tasks, in the same way the resolution of conflicts is important to generate productivity and harmony within the entity, that is why Secretaries must be in constant training in order to improve their management skills and techniques for conflict resolution. To carry out this research project, the surveys were used as a technique, which were used to the secretaries of the archive area, where key questions were formulated in order to obtain adequate information about the investigative topic, this with the purpose of collecting the necessary information to arrive at a conclusion that allows to identify the existing problems and in turn provide them with solutions, in order to improve the performance and development of the company. In the development of this research, it was possible to show the problems that affect the image of the CNT company, Babahoyo canton, one of them being the deficiency in the management and planning of digital and physical documents due to lack of knowledge in the secretaries, on the other On the other hand, the lack of execution in the software applied by the entity, causing a delay in the subsequent activities for which the commercial area is responsible, since conflicts increase and productivity and good work performance in said institution decrease.